2016
DOI: 10.1158/1557-3125.advbc15-a55
|View full text |Cite
|
Sign up to set email alerts
|

Abstract A55: Exosome-associated microRNAs as plasma biomarkers for breast cancer

Abstract: Introduction: microRNAs are promising candidate biomarkers due to their cancer-specific expression profiles. However, efforts to develop circulating breast cancer biomarkers are challenged by the heterogeneity of microRNAs in the blood. To overcome this challenge, we aimed to develop a molecular profile of microRNAs specifically secreted from breast cancer cells. The key to identifying breast cancer-derived microRNAs relies on capturing and analyzing the contents of exosomes, which are small secretory vesicles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Exosome is a critical biomarker in cancer diagnosis and progression. In cancer, exosomes play a critical role in tumor initiation, development, metastasis, and drug resistance. Numerous studies have shown distinct miRNA and exosomal protein indicators for many malignancies, including pancreatic cancer, prostate cancer, , lung cancer, breast cancer, , ovarian cancer, melanoma, glioblastoma, and pediatric cancer . The cancer markers on exosomes include protein (CD9, CD63, CD81, and other cancer-specific markers), nucleic acids (dsDNA, mRNA, and miRNA), and lipids.…”
Section: Introductionmentioning
confidence: 99%
“…Exosome is a critical biomarker in cancer diagnosis and progression. In cancer, exosomes play a critical role in tumor initiation, development, metastasis, and drug resistance. Numerous studies have shown distinct miRNA and exosomal protein indicators for many malignancies, including pancreatic cancer, prostate cancer, , lung cancer, breast cancer, , ovarian cancer, melanoma, glioblastoma, and pediatric cancer . The cancer markers on exosomes include protein (CD9, CD63, CD81, and other cancer-specific markers), nucleic acids (dsDNA, mRNA, and miRNA), and lipids.…”
Section: Introductionmentioning
confidence: 99%